Creating Katrina, rebuilding resilience lessons from New Orleans on vulnerability and resiliency - Zakour, Michael John; Mock, Nancy B.; Kadetz, Paul 1958- (Butterworth-Heinemann, 2018)
Creating Katrina, Rebuilding Resilience: Lessons from New Orleans on Vulnerability and Resiliency presents a unique, integrative understanding of Hurricane Katrina in the New Orleans area, and the progression to disaster vulnerability as well as resilience pathways. The book integrates the understanding of vulnerability and resiliency by examining the relationships among these two concepts and theories. The disaster knowledge of diverse disciplines and professions is brought together in this book, with authors from social work, public health, community organizing, sociology, political science, public administration, psychology, anthropology, geography and the study of religion. The editors offer both expert and an insider perspectives on Katrina because they have lived in New Orleans and experienced Katrina and the recovery. An improved understanding of the recovery and reconstruction phases of disaster is also presented, and these disaster stages have been the least examined in the disaster and emergency management literature.--Provided by publisher.